THE EFFECTIVENESS OF INDIRECT WRITTEN CORRECTION ON ENGLISH WRITING SKILLS - Aprillia Ariyanti (Journal of English for Academic and Specific Purposes (JEASP), 2018)
This study purposed to gain the difference between students’ academic performance in writing skills who are taught by using indirect written correction and those do not. The research design used quasi-experimental design because this study did not do randomization. In this experimental design, the researcher used two classes to become the subject. One class was experimental class which treated by using indirect correction technique while the other class was control class which was not treated by using indirect correction technique. The subject of this study was seven grade in MTs Pontren Surya Buana Malang.; 7C became control group and 7D was became experimental group. Both of groups consisted 24 students. Both of groups consisted 35 students. This data used t-test to find the significant difference of both groups.           The result was difference between two groups 17, 16 and the std. deviation difference is 0, 92.  T-test count =18, 591 t- table =1, 679 and p-value 0.000 α (0, 05). It applied that the technique was effective. The conclusion is indirect correction technique is effective to teach writing skills. Then, it is suggested to the teacher to apply or implement a different writing technique to practice and improve the students’ writing, especially by using corrective feedback that have been practiced before. The next researchers can use another technique in their research such as direct corrective feedback because this research uses indirect corrective feedback to improve writing skills